The Correlates of Financial Dollarization in Ghana - Acheampong*, Kennedy; Opoku, Ernest; Suryadi, Edi; -Okyireh, Theodore Oduro (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
This study aimed to investigate the correlation between the dollarization of Ghana's finances. The objects of this study are real output, interest rate differentials, real exchange rates, inflation, and financial developments. The research subjects are based on quarterly data from the World Development Index (WDI) and the Bank of Ghana (BOG) for the years 1999-2022. The research method uses the Autoregressive Distributed Lag (ARDL) approach for cointegration. This study finds that the driving factors for financial dollarization in Ghana are real output, interest rate differentials, real exchange rates, inflation, and financial developments. While the dollarization of Ghana's finances is constrained by factors such as inflation, exchange rates, and financial growth, the differential in interest rates and actual output increases the demand for foreign currency in Ghana. This study implies that much is expected from the monetary policy authorities, and there is a need for proper coordination of fiscal and monetary policies to curb the issue of dollarization of finance in Ghana. Keywords: Financial Dollarization; Foreign Currency; ARDL; Ghana; Exchange Rate Abstrak Tujuan dari penelitian ini adalah untuk menyelidiki korelasi dolarisasi keuangan Ghana. Objek penelitian ini yakni output riil, perbedaan suku bunga, nilai tukar riil, inflasi, dan perkembangan keuangan. Subjek penelitian didasarkan pada data triwulanan dari World Development Index (WDI) dan Bank of Ghana (BOG) untuk tahun 1999-2022. Metode penelitian menggunakan pendekatan Autoregressive Distributed Lag (ARDL) untuk kointegrasi. Studi ini menemukan bahwa faktor pendorong dolarisasi keuangan di Ghana adalah output riil, perbedaan suku bunga, nilai tukar riil, inflasi, dan perkembangan keuangan. Sementara dolarisasi keuangan Ghana dibatasi oleh faktor-faktor seperti inflasi, nilai tukar, dan pertumbuhan keuangan, perbedaan suku bunga dan output aktual meningkatkan permintaan mata uang asing di Ghana. Implikasi dari penelitian ini adalah banyak yang diharapkan dari otoritas kebijakan moneter, ada kebutuhan untuk koordinasi yang tepat dari kebijakan fiskal dan moneter untuk mengekang isu dolarisasi keuangan di Ghana. Kata Kunci: Dolarisasi Keuangan; Mata Uang Asing; ARDL; Ghana; Nilai Tukar